Polish cluster internationalization policy during the political transformation - Wiercioch, Magdalena (Polska polityka internacjonalizacji klastrów w warunkach transformacji, 2020)
The period of transformation in Poland caused the increased interest in cluster policy. Initially, the focus was on their local development, but in later years the need to internationalize Polish cluster structures was increasingly emphasized. Clusters, which are a platform for cooperation and competition, have become an area of dynamic development of enterprises, and the Polish state has undertaken a number of initiatives to support them in the implementation of international initiatives. The aim of the study was to attempt to evaluate the Polish cluster policy over the 30 years of political transformation, with particular emphasis on the policy of cluster internationalization. For this purpose, the documents of the Polish Agency for Enterprise Development – Benchmarking of Clusters for 2010, 2012, 2014 and 2020 were analyzed. The author addressed the research question: Have Polish cluster structures been successfully internationalized during the 30 years of the political transformation?
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 148-159